Effect of coppice conversion into high forest on soil organic C and nutrients stock in a Turkey oak (Quercus cerris L.) forest in Italy. (15th June 2022) - Camponi, Lorenzo; Cardelli, Valeria; Cocco, Stefania; Serrani, Dominique; Salvucci, Andrea; Cutini, Andrea; Agnelli, Alberto; Fabbio, Gianfranco; Bertini, Giada; Roggero, Pier Paolo; Corti, Giuseppe
Abstract: In forest ecosystems, a variety of abiotic and biotic soil forming factors drives soil organic matter (SOM) and nutrients cycling with a profitable outcome on climate change mitigation. As a consequence, type and intensity of forest management, through its impact on carbon (C) and nutrient soil stocks, can be considered as an additional soil forming force. In this study, we investigated the influence of the coppice conversion into high forest on pedogenesis and on soil C and nutrient (N, P, Ca, Mg, and K) stocks, fifty years later the beginning of the conversion-cycle. The trial was established in a Turkey oak forest historically managed under the coppice system in central Italy. Specifically, we considered tree population density (natural evolution – control, moderate thinning, heavy thinning) where soil samples were collected according to genetic horizon to estimate C, N, and P stocks both in the forest floor and at fixed depth intervals (0–30, 30–50 and 50–75 cm). Further, the stocks of exchangeable Ca, Mg, and K were also assessed for the mineral layers. The results showed that litter and the upper layer of mineral soil (0–30 cm) contained a similar quantity of C (about 74–83 Mg ha -1 ), independently of the trials and no differences were observed also in the whole soil stocks (about 192–213 Mg ha −1 ). The comparison of the mean stocks calculated per 1-cm of thickness of organic (O), organo-mineral (OM), and mineral (M) layers, although it did not display any difference among trials (excepted for P and Mg), showed a similar capability of the organo-mineral horizons to store C and nutrients compared with the organic ones (e.g., about 6–12 Mg ha −1, 0.3–0.5 Mg ha −1 and 0.5–1.5 kg ha −1 for C, N and P, respectively). Our findings showed that thinning operated on Turkey oak coppice did not affect soil capacity to store C and nutrients. These results suggested that the forest ecosystem itself is the main soil forming force and this is consistent with the target of adopting forest management able to control the global C cycle through the storage of SOM in the mineral soil rather than in forest floor, where SOM turnover is faster. Highlights: Thinning of Turkey oak forest has negligible effect on soil C and nutrients stock. Genetic horizons are fundamental in determining soil C and nutrient stock. Mineral horizons of forest soils are able to store high amount of organic C in depth. The multi millennial forest cover is the main soil forming factor.